The Past, Present, and Future of Kingella kingae Detection in Pediatric Osteoarthritis - Pablo Yagupsky (Diagnostics, 2022)
As a result of the increasing use of improved detection methods, Kingella kingae, a Gram-negative component of the pediatric oropharyngeal microbiota, is increasingly appreciated as the prime etiology of septic arthritis, osteomyelitis, and spondylodiscitis in children aged 6 to 48 months. The medical literature was reviewed to summarize the laboratory methods required for detecting the organism. Kingella kingae is notoriously fastidious, and seeding skeletal system samples onto solid culture media usually fails to isolate it. Inoculation of synovial fluid aspirates and bone exudates into blood culture vials enhances Kingella kingae recovery by diluting detrimental factors in the specimen. The detection of the species has been further improved by nucleic acid amplification tests, especially by using species-specific primers targeting Kingella kingae’s rtxA, groEL, and mdh genes in a real-time PCR platform. Although novel metagenomic next-generation technology performed in the patient’s plasma sample (liquid biopsy) has not yet reached its full potential, improvements in the sensitivity and specificity of the method will probably make this approach the primary means of diagnosing Kingella kingae infections in the future.